2016
DOI: 10.1515/botcro-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

Embryological features, pollen and seed viability of Arnica montana (Asteraceae) – a threatened endemic species in Europe

Abstract: -The embryological features, mode of reproduction and reproductive capacity (pollen and seed viability) on two naturalized populations of Arnica montana in Bulgaria were studied. The embryological study shows that A. montana is a facultative apomictic species in which sexual reproduction predominates. In this species, it was established that there is a comparatively high viability of the mature pollen and embryos, which enables the successful realization of its reproductive capacity. The results of the study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…is a circumboreal genus of about 30 species mostly of montane habitats. Arnica montana L. (Asteraceae, mountain arnica, wolfs' bane) is a perennial, facultative apomictic species (Yankova-Tsvetkova et al 2016), predominantly self-incompatible, insect pollinated which reproduces sexually with seeds and vegetatively with short rhizomes (Luijten et al 1996(Luijten et al , 2000. A. montana grows on acidic grass-and shrublands and is distributed from the Iberian Peninsula to the Ukraine (Maurice et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…is a circumboreal genus of about 30 species mostly of montane habitats. Arnica montana L. (Asteraceae, mountain arnica, wolfs' bane) is a perennial, facultative apomictic species (Yankova-Tsvetkova et al 2016), predominantly self-incompatible, insect pollinated which reproduces sexually with seeds and vegetatively with short rhizomes (Luijten et al 1996(Luijten et al , 2000. A. montana grows on acidic grass-and shrublands and is distributed from the Iberian Peninsula to the Ukraine (Maurice et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The germination of seeds of S. scardica under natural conditions is also poor [41]. Studies on the seed germination of several Sideritis species [42,43] have revealed a strong correlation between germination and environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…La última revisión de la bibliografía embriológica de Asteraceae corresponde a Johri et al (1992). Entre los trabajos de embriología publicados posteriormente cabe mencionar Ao et al (2009), Battjes et al (1994), Bonifacio et al (2018), Deng et al (2010), Franca et al (2015), Gotelli et al (2008), Pacini & Keijzer (1989), Sun et al (1987), Yankova-Tsvetkova et al (2016, 2017, Yurukova-Grancharova (2004), Yurukova-Grancharova et al (2006, Yeung et al (2011).…”
Section: Ausente O Residualunclassified
“…En todos los taxones analizados el endotecio y la epidermis son persistentes durante la dehiscencia y están más engrosadas en los lóculos externos. Sin embargo, en Asteraceae puede haber especies que solo mantengan el endotecio y no la epidermis (Yankova-Tsvetkova et al, 2016).…”
Section: Mecanismo De Dehiscencia De Las Anteras: El Endotecio Y El T...unclassified